Trends and seasonal variability of atmospheric NO2 and HNO3 concentrations across three major African biomes inferred from long-term series of ground-based and satellite measurements. (15th June 2019) - Ossohou, M.; Galy-Lacaux, C.; Yoboué, V.; Hickman, J.E.; Gardrat, E.; Adon, M.; Darras, S.; Laouali, D.; Akpo, A.; Ouafo, M.; Diop, B.; Opepa, C.
Abstract: In the framework of the INDAAF (International Network to study Deposition and Atmospheric chemistry in AFrica) programme, part of the ACTRIS European Research Infrastructure for the long-term observation of Aerosols, Cloud, and Trace gases, this paper aims to study trends and seasonal variability of surface atmospheric NO2 and HNO3 concentrations, and OMI (Ozone Monitoring Instrument) NO2 over 6 sites in tropical Africa. Sites are located in west and central Africa to represent the major African biomes: dry savanna (Banizoumbou, Niger and Katibougou, Mali), wet savanna (Djougou, Benin and Lamto, Côte d'Ivoire) and forest (Bomassa, Republic of Congo and Zoétélé, Cameroon). Ground-based NO2 and HNO3 concentrations were obtained over the period 1998–2015 using INDAAF passive samplers at a monthly basis, and NO2 Vertical Column Densities (VCDs) from OMI for a 1° grid cell around each sites were obtained from 2005 to 2015. Mean annual NO2 concentrations ranged from 2.3 ± 1.2 to 0.9 ± 0.4 ppb from dry savannas to forests, representing a north south gradient. In dry savannas, we observe two concentration peaks of NO2 appearing at the beginning and the end of the wet season both for ground-based and satellite measurements, whereas at wet savannas and forest sites, NO2 concentrations are highest in the dry season. The seasonality of surface NO2 observations provide further evidence for a large role of microbial soil NOx emissions in dry savannas and of biomass burning NOx emissions in wet savanna and forest sites. Mean annual HNO3 concentrations ranged from 0.4 to 0.5 ppb in dry and wet savannas to 0.2–0.3 ppb in forest. In dry ecosystems, higher HNO3 concentrations are measured in the early wet season, consistent with NO2 results. The analysis of a long-term dataset of surface O3 concentrations indicates that HNO3 production can mainly be explained by the photooxidation of NOx . Mann-Kendall and Seasonal Kendall statistical tests showed that NO2 surface concentrations have a significant decreasing seasonal and annual trends at multiple sites ( p-value < 0.05) ranging from −2.96% yr −1 (at Zoétélé) to −0.64% yr −1 (at Banizoumbou). HNO3 results indicate no trends except at Bomassa (1.07% yr −1 ). The decreasing NO2 ground-based concentration trends observed in wet savannas sites are correlated with OMI NO2 decreasing trends at these sites. Trends obtained for NO2 concentrations in wet savanna and forest ecosystems are consistent with trends of NOₓ biomass burning emissions. Highlights: Long term data of surface and column nitrogenous gases from major African biomes. North-South latitudinal negative gradient in surface concentrations of NO2 and HNO3 . Microbial soil emissions of NOₓ are predominant in dry savannas. Biomass burning emissions of NOx are predominant in wet savanna and forest sites. NO2 annual and seasonal decreasing trends at most of west and central Africa sites.